Disparitas Gender dalam Kecelakaan Lalu Lintas Kerja: Integrasi Perspektif Gender pada Kerangka Safe System di Kota Batam - Vito Raegentsario; Sari, Yusra Aulia; Rifai, Andri Irfan (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Work-related traffic accidents represent a significant public health and economic issue in rapidly urbanising areas like Batam City, Indonesia. As a major industrial and trade hub, Batam experiences high volumes of commuter traffic, exacerbating road safety challenges. Despite this, a critical gap exists in current research and policy where gender-specific vulnerabilities—including differences in risk perception, vehicle choice, and travel patterns—are often overlooked. This study aims to fill this gap by investigating these nuanced gender disparities in work-related traffic accidents in Batam. Furthermore, it seeks to propose actionable strategies for systematically integrating gender considerations into the established Safe System framework, thereby providing evidence-based recommendations for stakeholders. A quantitative research design was employed, utilising a structured questionnaire distributed via Google Forms to a cohort of 498 randomly sampled workers in Batam City. The collected data were analysed using descriptive statistics and simple linear regression in SPSS. The analysis specifically examined the relationship between positive safety perceptions and experiences (BTHD) and workers' perceived vulnerability and wariness (BTHC) during their commute. The results revealed a statistically significant positive relationship (B = 0.626, p < .001). Counter-intuitively, this indicates that as respondents' positive safety perceptions increased, their self-reported level of wariness and alertness also rose. This key finding suggests that a sense of safety among Batam's workforce is not a passive state leading to complacency but is actively constructed upon a state of heightened awareness. The study concludes that achieving the goal of zero fatalities requires the Safe System approach to evolve beyond physical infrastructure to incorporate these complex psychological drivers and gender-specific factors. These findings offer policymakers critical insights for developing more inclusive, equitable, and effective road safety interventions.